2014
DOI: 10.1557/opl.2014.232
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adherence Steels Hardened Superficially

Abstract: This study evaluates the behavior of the adherence layers -sawn flat iron boride formed on the surface of steels used in manufacturing industry in Mexico. In steels AISI 1018, AISI 8620 and AISI 316 was characterized this behavior, boriding thermochemical treatment with box technique, with a processing temperature of 1273 °K, with an exposure time of 8 hours. Furthermore the adherence is assessed by the Rockwell C hardness technique prescribed by the German standard VDI 3198 of traction, this impact test quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…where CI K is the fracture toughness, ( P ) is the indentation load, ( g ) is the crack length generated on corners of the indentation, ( l ) is the half of the diagonal length of the indenter, crack length measured from the center of the tread indenter ( C ) , ( E ) is the elastic modulus on iron boride phase on AISI 8620 is 292.25±2.75 GPa obtained in [5], ( H ) is the hardness of the material and H .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where CI K is the fracture toughness, ( P ) is the indentation load, ( g ) is the crack length generated on corners of the indentation, ( l ) is the half of the diagonal length of the indenter, crack length measured from the center of the tread indenter ( C ) , ( E ) is the elastic modulus on iron boride phase on AISI 8620 is 292.25±2.75 GPa obtained in [5], ( H ) is the hardness of the material and H .…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the hard coatings obtained on AISI 8620 surface is effective in the treatment conditions, to a temperature of 1223 K with times of 6 to 8 h, as they have the acceptable quality of adhesion (HF4) while for the condition of 1273 K with the times of 6 to 8 h, have the quality of insufficient adhesion (HF5) due to the presence of CrB, MnB in the borided layer. The work done by N. Lopez et al [12] and D. Sanchez et al [5] obtained as a result on AISI 8620 steels borided through powder pack boride process, their results show the presence of FeB and Fe 2 B phases and in condition of 1273 K have optimal adhesion (HF1-HF4) but Taktak et al [13] found that their adhesion decreased with an increase of boriding time and temperature on H13 and AISI 304 steels boriding.…”
mentioning
confidence: 98%